Estrategias efectivas de liderazgo para promover el uso de la tecnología educativa en los niveles de educación general básica de la Unidad Educativa “González Suárez” de la parroquia Chuquibamba para el periodo 2023-2024 - Zaragocín Martínez, Diego Alfonso (2024)
The study focuses on "Effective leadership strategies to promote the use of educational technology" in the Unidad Educativa "González Suárez" of the Chuquibamba Parish. Given the growing interdependence between education and technology, the institution, located in a rural area, has limited access to technology and faces the challenge of effectively integrating these tools in its educational process. The research seeks to advance in the knowledge of the relationship between pedagogical leadership and educational technology, proposing specific strategies adapted to the institution to improve the quality of teaching and prepare students for a digital environment. It is justified by the need to address the lack of effective leadership in the implementation of educational technology, identifying innovative approaches to boost its adoption. Aimed at educational leaders and teachers, the research contributes to the fourth Sustainable Development Goal (SDG), focused on improving educational quality through technology integration. In addition, it is in line with the research line of the Master's Degree in Education of the Universidad Nacional de Loja (U.N.L.), which seeks to exercise leadership to empower and improve educational situations. The specific objectives include diagnosing the level of integration of educational technologies in the Unidad Educativa "González Suárez" and from there designing effective leadership strategies. The methodology adopts a descriptive and correlational approach, using analytical-synthetic, inductive and deductive methods. The target population is teachers, including administrators and students of basic general education during the academic period September-November 2023. The research is supported by techniques such as observation and surveys, applied to the aforementioned groups of teachers, students and administrative staff. The process is divided into phases, from the determination of the problem to the analysis of data to obtain results. With the purpose of improving the integration of educational technology, this study aims to offer practical and applicable guidelines for educational leaders, contributing to the preparation of students for an increasingly digitized world.